2020
DOI: 10.1002/prep.202000154
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Void Orientation in Uniaxially Pressed PBX 9502

Abstract: Ultra-and small-angle neutron scattering techniques were used to study the morphology of voids in directions parallel and perpendicular to the compaction plane of a uniaxially pressed cylinder of PBX 9502. Two-dimensional scattering patterns from samples cut parallel to the compaction plane had circular equal-intensity contours, implying that along this view the voids are circular or randomly oriented. Identical measurements of samples cut perpendicular to the compaction plane produced elliptical equalintensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This projection produces isotropic scattering. However, previous measurements [19] made with neutrons incident perpendicular to the pressing direction revealed that the scattering intensity in this direction is dependent upon the direction of Q ( Q ), and that the Porod Invariant is two‐dimensional. Application of Eq.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This projection produces isotropic scattering. However, previous measurements [19] made with neutrons incident perpendicular to the pressing direction revealed that the scattering intensity in this direction is dependent upon the direction of Q ( Q ), and that the Porod Invariant is two‐dimensional. Application of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…A simple two‐phase approach can be used to describe the observed scattering [22]. The two‐phase approximation can also be used for PBX 9502 ( ρ =4.83×10 10 cm −2 ) samples, as the difference in scattering length density between TATB and Kel‐F 800 ( ρ =3.98×10 10 cm −2 ) is small, and contributes little to the scattering signal [19]. The observed scattering arises from the void phase, although in this case, it is contrasted against the TATB/Kel‐F 800 matrix.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations